Spatial Analysis of Air Pollution in selected Central European countries - Egwuchukwu, Melody Ogechi (2024)
This thesis investigates the spatial analysis of air pollutants (Carbon Monoxide (CO), Ozone (O3), and Nitrogen Dioxide (NO2)) across selected Central European countries, focusing on their correlation with population density. Utilizing spatial analysis techniques and statistical analyses, the study examines the geographic distribution, spatial patterns, and relationships between air pollutant concentrations and population size.